Representasi Nilai-Nilai Budaya Melayu dalam Interaksi Sosial Anak Usia Dini melalui Aktivitas Bermain - Erni, Erni; Fadillah, Siti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to describe the representation of Malay cultural values in early childhood social interaction through play activities at TK Negeri Pembina 3 Pekanbaru. The background of this research is based on the phenomenon of low social interaction skills among children and the decreasing interest in traditional games due to the influence of modern and digital games. This study employed a qualitative approach with a descriptive method. The research subjects were 15 children aged 5–6 years in group B, selected using purposive sampling. Data were collected through observation, interviews, and documentation. Data analysis was conducted using the model of Miles, Huberman, and Saldana, which includes data reduction, data display, and conclusion drawing. The results indicate that Malay cultural values such as politeness, togetherness, mutual cooperation, respect, helping behavior, and cooperation are represented through traditional play activities such as congkak, jump rope, and engklek. These play activities improve children’s social interaction skills, including communication, turn-taking, sharing, cooperation, and simple conflict resolution. Therefore, it can be concluded that play activities based on Malay culture play an important role in instilling cultural values and developing social interaction in early childhood.